2020
DOI: 10.2174/0929866527666200613215449
|View full text |Cite
|
Sign up to set email alerts
|

Triple-A Syndrome (TAS): An In-Depth Overview on Genetic and Phenotype Heterogeneity

Abstract: : Triple-A Syndrome (TAS) is a rare autosomal recessive disorder characterized by three cardinal symptoms: alacrimia, achalasia and adrenal insufficiency due to ACTH insensitivity. Various progressive neurological abnormalities and skin changes have been described in association with the syndrome. The disease is caused by mutation in the AAAS gene on chromosome 12q13. Mutations in AAAS were identified in more than 90% of individuals and families with TAS. The protein encoded by AAAS was termed ALADIN and is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 131 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, despite having the same variant (AAAS: c.1331+1G>A), North African Triple-A patients manifested phenotypic variability of the disease, suggesting a lack of genotype-phenotype correlation [Kallabi et al 2016a[Kallabi et al , 2016bBenabdallah et al, 2014;Berrani et al, 2018;Alakeel et al, 2015]. In fact, in the current literature, the high phenotypic heterogeneity even among members of the same family is rather well known for Triple-A [Barat et al, 2004;Brooks et al, 2005;Singh et al, 2018;Pogliaghi et al, 2020].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, despite having the same variant (AAAS: c.1331+1G>A), North African Triple-A patients manifested phenotypic variability of the disease, suggesting a lack of genotype-phenotype correlation [Kallabi et al 2016a[Kallabi et al , 2016bBenabdallah et al, 2014;Berrani et al, 2018;Alakeel et al, 2015]. In fact, in the current literature, the high phenotypic heterogeneity even among members of the same family is rather well known for Triple-A [Barat et al, 2004;Brooks et al, 2005;Singh et al, 2018;Pogliaghi et al, 2020].…”
Section: Discussionmentioning
confidence: 91%
“…Triple-A syndrome (also named Allgrove syndrome), another autosomal recessive disorder involving primary adrenal insufficiency (due to an ACTH resistant status), is a very rare condition with underlying mutations of the AAA (or AAAS) gene on chromosome 12q13 in 90% of cases; it also includes alacrimia (defects of tear formation) and (esophageal) achalasia, which induces difficulties of swelling, dry mouth, and vomiting due to esophagitis with potential dental damage [ 157 , 158 , 159 , 160 ]. Tadini et al reported a case of triple-A syndrome associated with peculiar dental anomalies [ 161 ].…”
Section: Methodsmentioning
confidence: 99%